Effect of the angiotensin receptor–neprilysin inhibitor sacubitril/valsartan on the pharmacokinetics and pharmacodynamics of a single dose of furosemide. (20th February 2018) - Ayalasomayajula, Surya; Schuehly, Uwe; Pal, Parasar; Chen, Fabian; Zhou, Wei; Sunkara, Gangadhar; Langenickel, Thomas H.
Abstract : Aims: Sacubitril/valsartan is indicated for the treatment of heart failure and reduced ejection fraction (HFrEF). Furosemide, a loop diuretic commonly used for the treatment of HFrEF, may be coadministered with sacubitril/valsartan in clinical practice. The effect of sacubitril/valsartan on the pharmacokinetics and pharmacodynamics of furosemide was evaluated in this open label, two‐period, single‐sequence study in healthy subjects. Methods: All subjects ( n = 28) received 40 mg oral single‐dose furosemide during period 1, followed by a washout of 2 days. In period 2, sacubitril/valsartan 200 mg (97/103 mg) was administered twice daily for 5 days and a single dose of 40 mg furosemide was coadministered on day 6. Serial plasma and urine samples were collected to determine the pharmacokinetics of furosemide and sacubitril/valsartan and the pharmacodynamics of furosemide. The point estimates and the associated 90% confidence intervals for pharmacokinetic parameters were evaluated. Results: Coadministration of furosemide with sacubitril/valsartan decreased the maximum observed plasma concentration (Cmax ) [estimated geometric mean ratio (90% confidence interval): 0.50 (0.44, 0.56)], area under the plasma concentration–time curve (AUC) from time 0 to infinity [0.72 (0.67, 0.77)] and 24‐h urinary excretion of furosemide [0.74 (0.69, 0.79)]. When coadministered with sacubitril/valsartan, 0–4‐h, 4–8‐h and 0–24‐h diuresis in response to furosemide was reduced by ~7%, 21% and 0.2%, respectively, while natriuresis was reduced by ~ 28.5%, 7% and 15%, respectively. Post hoc analysis of the pivotal phase III Prospective comparison of ARNI with ACEI to Determine Impact on Global Mortality and morbidity in Heart Failure trial (PARADIGM‐HF) indicated that the median furosemide dose was similar at baseline and at the end of the study in the sacubitril/valsartan group. Conclusions: Sacubitril/valsartan reduced plasma Cmax and AUC and 24‐h urinary excretion of furosemide, while not significantly affecting its pharmacodynamic effects in healthy subjects.